Association of Specific Traumatic Experiences With Alcohol Initiation and Transitions to Problem Use in European American and African American Women. (22nd September 2016) - Werner, Kimberly B.; Sartor, Carolyn E.; McCutcheon, Vivia V.; Grant, Julia D.; Nelson, Elliot C.; Heath, Andrew C.; Bucholz, Kathleen K.
Abstract : Background: The aims of this study were to (i) characterize racial differences in alcohol involvement and (ii) examine the risk conferred by specific trauma exposures and posttraumatic stress disorder (PTSD) for different stages of alcohol involvement in European American (EA) and African American (AA) women. Methods: Data are from the Missouri Adolescent Female Twins Study ( N = 3, 787, 14.6% AA; mean age at most recent interview = 24.5 [SD 2.8]). Trauma exposures (e.g., sexual abuse [SA], physical abuse [PA], witnessing another person being killed or injured, experiencing an accident, and experiencing a disaster) were modeled as time‐varying predictors of alcohol initiation, transition to first alcohol use disorder (AUD) symptom, and transition to AUD diagnosis using Cox proportional hazards regression while taking into account other substance involvement, parental characteristics, and commonly co‐occurring psychiatric disorders. Results: In EA women only, SA was associated with alcohol initiation prior to the age of 14, PA predicted transition from initiation to first AUD symptom, and PA, witnessing injury or death, and SA predicted transition to AUD diagnosis. No association was discovered between trauma exposures or PTSD for any stage of alcohol involvement in AA women. Conclusions: Results reveal trauma experiences as important contributors to all stages of alcohol involvement in EA women only, with different trauma types conferring risk for each stage of alcohol involvement. PTSD was not revealed as a significant predictor of AUD in EA or AA women, suggesting trauma, independent of PTSD, directly contributes to alcohol involvement. Findings highlight the importance of considering racial differences when developing etiologic models of the association of traumatic experiences with alcohol involvement. Abstract : We examined the risk conferred by specific trauma exposures and PTSD for stages of alcohol involvement in European American (EA) and African American women ( n = 3, 787; mean age 24.5 years; 85.4% were EA). Results show that interpersonal trauma experiences are important contributors to all stages of alcohol involvement in EA women only. Findings highlight the role of trauma experiences in alcohol‐related pathology and the importance of considering race when considering the link between traumatic experiences and alcohol involvement.